2006
DOI: 10.18474/0749-8004-41.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Host-Free Survival of Boll Weevils (Coleoptera: Curculionidae) Previously Fed Vegetative-Stage Regrowth Cotton

Abstract: The need to minimize populations of overwintering boll weevils (Anthonomus grandis Boheman) in eradication programs is widely recognized, but the potential contribution of nonfruiting regrowth cotton (Gossypium hirsutum L.) to weevil survival has not been directly examined. We conducted experiments in 2002 and 2003 to examine the host-free survival of weevils previously supplied vegetative-stage regrowth cotton. Weevils, 1–3 d after eclosion, were caged with vegetative regrowth cotton under ambient environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The higher host-free survival rates of males compared with females are difficult to interpret unambiguously, especially considering that several previous studies using either vegetative stage cotton as food ( Esquivel et al 2004 , Suh and Spurgeon 2006 ) or observations of survival under ambient conditions ( Westbrook et al 2003 , Spurgeon 2008 ) did not report similar differences. Regardless, differences observed in this study occurred early in the host-free survival period.…”
Section: Discussionmentioning
confidence: 90%
“…The higher host-free survival rates of males compared with females are difficult to interpret unambiguously, especially considering that several previous studies using either vegetative stage cotton as food ( Esquivel et al 2004 , Suh and Spurgeon 2006 ) or observations of survival under ambient conditions ( Westbrook et al 2003 , Spurgeon 2008 ) did not report similar differences. Regardless, differences observed in this study occurred early in the host-free survival period.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have demonstrated extended host-free survival attributed to diet-induced diapause ( Suh and Spurgeon 2006 , Spurgeon et al 2008 , Spurgeon and Suh 2017 ). In addition, the duration of the induction period during which the weevils feed (D.W.S., unpublished data) and the temperature during this feeding period ( Spurgeon and Suh 2017 ) have been shown to influence subsequent survival.…”
Section: Discussionmentioning
confidence: 99%
“…One carton each of males and females, both fed the same diet, were combined in each of 14 survival cages. Cages were held in environmental chambers at 23.9 ± 1°C with a photoperiod of 13:11 (L:D) h. This temperature was selected based on results of Spurgeon et al (2008) and Suh and Spurgeon (2006) , because it produces mortality at a sufficiently low rate to distinguish relevant differences among treatments without unnecessarily prolonging the duration of the experiment. Each cage was inspected at 7-d intervals to remove dead weevils.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations